EXPERIMENTAL PERFORMANCE FLEXURE STRESS OF FERRO CEMENT BEAM WITH NUMBER OF LAYER MESH - Bhakare Vishal .S.; Bhakare Vikaram .S; Adlinge Sharad .S. (International Journal of Innovations in Engineering Research and Technology, 2022)
The present study describes the results of testing Ferro cement beam reinforced with different number of wire mesh layers. The main objective of this work is to study the effect of using different no of wire mesh layers on the flexural strength of Ferro cement beam and to compare the effect of varying the no of wire mesh layers. The no of layers used are one, two, three, four, and five up to twelve layers of mesh used in beams. The beam moulds size is 700*150*150 with welded square mesh with varying no of layers of mesh. Beams were casted with mortar of mix proportions (1:2) and water cement ratio (0.38). There is no super plasticizer use in casting. Beams were tested under two-point loading system in UTM Machine after curing period of 28 days. Test result shows that beams with more no of layers exhibits greater flexural strength and less deflection. There are increase in load carrying capacity, ductility and reduces the weight of beams